Global Evaluation of Internet Banking Research: A Scientometric Study on Trends, Growth and Impact - Mueen, Ahmed KK; Boraiah, G.B; Sateesha, H; Chandrashekara, M; Chaman, Sab M (Information Research Communications, 2024)
Aim The paper assesses the global research output on “Internet banking” indexed in the Claravite Analytics Web of Science (WoS) database. Materials and Methods The Web of Science Database searched for articles published in global research output. Results The 922 global internet banking was published from 2005 to 2024 and was cited 34,487 times, with an Average Citation per Paper (ACP). Internet banking received external funding support and was involved in international collaboration. The Most productive organization was the Indian Institute of Management IIM system, New Delhi, The Most productive journal was the International Journal of Bank Marketing with n=55 (5.96%), The most productive country was Peoples R China n =184 publications (19.957%), CONCLUSION This study has identified core and significant authors, organizations, journals, document type, country collaborations and subject fields and significant keywords.
Keywords: Global Evaluation; Internet banking; Scientometric analysis; Growth trends; Impact